Epsin bioactive coating reduced in-stent intimal hyperplasia by promoting early phase reendothelialization and inhibiting smooth muscle cell proliferation - Wenxu Zhang; Hao Lin; Zechao Zhu; Kunyuan Zhu; Shijun Bi; Xinyu Yang; Guangzhi Hao; Dandan Gao; Da Huo; Shanshan Chen; Jing Zhao; Meixia Liu; et al. (PLoS ONE, 2025)
In recent years, interventional surgery has become a treatment for ischemic stroke due to its low risk of injury. However, the occurrence of restenosis hinders the long-term effectiveness and safety of stent implantation. At present, drug-eluting stents mainly prevent the stenosis of drug-eluting stents by inhibiting the proliferation of smooth muscle cells (SMCs). However, these drugs cause damage to endothelial cells (ECs), prevent timely re endothelialization of blood vessels, and increase the risk of late thrombosis and late restenosis. EPS-15-interacting protein 1 (Epsin1)- EPS-15-interacting protein 2 (Epsin2)-shrna coated stents have the potential to promote early endothelialization and inhibit restenosis, which contributes to the candidate development of novel drug coated stents. We found that the expression of Epsin was elevated in the mouse carotid artery ligation model, and the intimal hyperplasia(IH) could be reduced by intervening Epsin. Epsin in cultured endothelial cells was interfered to study proliferation and migration functions, and its role in cocultured endothelial cells and smooth muscle cells was evaluated. In addition, we explored the potential therapeutic benefits of inhibiting Epsin in a porcine model using scaffolds coated with plasmids containing Epsin short hairpin RNA (shRNA). Our study showed that the expression of Epsin1 and Epsin2 was elevated in the proliferative intima of mice, and the inhibition of Epsin reduced the proliferation of neointima in mice. The inhibition of Epsin led to enhanced proliferation and migration of endothelial cells, and maintained a healthy cell membrane potential. In cocultured cells, inhibition of Epsin resulted in reduced proliferation and migration of smooth muscle cells. In a porcine carotid artery model, Epsin shRNA coated scaffolds promoted early re endothelialization and reduced IH. These results suggest that Epsin plays a crucial role in endothelial and smooth muscle cell proliferation and migration functions, and its inhibition may be a potentially effective therapeutic strategy to prevent in stent stenosis.